2021
DOI: 10.1088/2053-1591/abd731
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of interfacial structure of the joints between a tungsten-copper composite and austenitic stainless steel

Abstract: Joining of CuW70 composite and 0Cr18Ni9 stainless steel was successfully achieved at temperatures 1150 °C with durations from 15 to 90 min after adding a pure copper intermediate layer. Microstructure, phase composition and elemental distribution at the interfacial region were studied. The optimum joining interface with a dense microstructure was obtained at a joining temperature of 1150 °C with a duration of 60 min. Interdiffusion of atoms occurred at the interface between the tungsten-copper composite and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Residual stress was minimized in this configuration, and it was hypothesized that, during the cooling period, vanadium would transfer the residual stress from tungsten and eventually Cu would relieve the residual stress through plastic deformation. A Cu interlayer has also been used in diffusion bonds between the W-Cu composite and stainless steel at 1150 • C for different holding times [109]. It was found that the elements from the steel side exhibit intergranular diffusion while penetrating the Cu interlayer.…”
Section: Copper Interlayermentioning
confidence: 99%
“…Residual stress was minimized in this configuration, and it was hypothesized that, during the cooling period, vanadium would transfer the residual stress from tungsten and eventually Cu would relieve the residual stress through plastic deformation. A Cu interlayer has also been used in diffusion bonds between the W-Cu composite and stainless steel at 1150 • C for different holding times [109]. It was found that the elements from the steel side exhibit intergranular diffusion while penetrating the Cu interlayer.…”
Section: Copper Interlayermentioning
confidence: 99%
“…The diverse nature of both materials is dominant during fusion welding processes. However, considerable effort has been made to join copper to stainless steel via fusion welding processes [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Overall, it is safe to conclude that the metallurgy of copper to stainless steel joints must be the researcher’s focus when welding them with fusion welding processes.…”
Section: Introduction—joining Of Copper To Stainless Steel Bimetallic...mentioning
confidence: 99%